A strategy for rural development: The Didactic Farms in Italy - Santucci, Fabio Maria; Ascani , Michela (Advances in Social Sciences Research Journal, 2021)
This paper analyses the recent development and the main features of the Didactic farms in Italy, where this type of on-farm activities is recognized by Law since 1985, as one of the diversification strategies for rural development. It is a sort of informal education, where the farmers, their family members and other collaborators act as teachers, mainly for organized groups of kids and teenagers. In Italy, this type of farms and their didactic programs, which last from a few hours to several days, can be formally recognized by the Regional Governments and this recognition opens the door to a) formal collaborations with the kindergardens and schools, and b) possibility to apply for grants to improve structures and purchase equipments. In the last two decades, the number of didactic farms has increased from 276 in year 2000 to 3,120 in 2020, scattered all over the country, whereas in the same period the total number of farms has fallen by 32 percent. Didactic schools should be considered and supported during the next EU programming period 2021-2026, as they were in the past.